Thecamoebians in Lake Winnipeg: A tool for holocene paleolimnology - Burbidge, S.M. (Susan M.); Schroder-Adams, C. (Claudia) (1998)
Holocene sediments in Lake Winnipeg are expressed in the lower Lake Agassiz sequence which is unconformably overlain by the Lake Winnipeg sequence. Nine sites, covering the North and South basins and the connecting Narrows, were selected for analysis of Holocene changes in thecamoebian faunae. Only the Lake Winnipeg sequence contains thecamoebians. This study indicates that biologic productivity and consequently the type of organic material in the sediments is the main control on thecamoebian taxa in Lake Winnipeg. Other factors controlling the distribution of thecamoebians are water chemistry and turbidity. Inorganic sediment geochemistry and water temperature do not appear to significantly influence the thecamoebian fauna of Lake Winnipeg. Variations in the abundance of key thecamoebian species along a north-south transect divide Lake Winnipeg into three distinct areas. The North Basin has remained relatively unchanged since the retreat of Lake Agassiz as indicated by the domination of Difflugia manicata throughout its history. This species appears to prefer Cyanophyta and diatoms as its food source. In the Narrows harsh conditions created by turbid waters and lack of algal food taxa result in Centropyxis aculeata replacing Difflugia manicata as the dominant species. In the South Basin three thecamoebian assemblages are recognized. Cucurbitella tricuspis, indicative of eutrophic conditions, dominates the most recent sediments of the South Basin. The underlying sediments are characterized by Difflugia globulus. In Lake Winnipeg this species is not a cold climate (arctic) indicator as suggested elsewhere but instead seems to prefer sediments containing green and yellow-green algal material. A Centropyxis-Arcella Assemblage occurs only at the base of the southernmost core where it is indicative of an early phase of hyposaline conditions as developed in shallow pools during the southward transgression of Lake Winnipeg. This study illustrates the usefulness of thecamoebians as paleolimnological indicators. Environmental changes are more significant in the restricted South Basin resulting in distinct thecamoebian assemblages. In contrast, the North Basin provided a stable environment throughout the late Holocene reflected in only subtle faunal changes.